2006
DOI: 10.1681/asn.2005121342
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulotubular Junction Abnormalities Are Associated with Proteinuria in Type 1 Diabetes

Abstract: Glomerulotubular junction abnormalities, frequent in proteinuric patients with type 1 diabetes, may contribute to the progressive GFR loss in overt diabetic nephropathy. Glomerulotubular junction abnormalities were examined in patients who have type 1 diabetes with a wide range of albumin excretion rates (AER). Renal biopsies from five normoalbuminuric patients, five microalbuminuric patients, six proteinuric patients, and five control subjects were studied by light and electron microscopy. Light microscopy sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 29 publications
(31 reference statements)
2
64
1
Order By: Relevance
“…Atubular glomeruli are commonly observed in various types of CKD, [41][42][43][44] and also reported in animal models of tubular injury. 45,46 Our data indicate that selective proximal tubule injury is sufficient to cause atubular glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Atubular glomeruli are commonly observed in various types of CKD, [41][42][43][44] and also reported in animal models of tubular injury. 45,46 Our data indicate that selective proximal tubule injury is sufficient to cause atubular glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…Additional abnormalities include global glomerular sclerosis [23] and interstitial expansion [21]. More recently, we reported that the onset of proteinuria is associated with the development of new glomerular lesions, specifically, widespread abnormalities of the junction of the proximal tubule with the glomerulus, which ultimately lead to separation of the glomerulus from its tubule (atubular glomeruli) and, thus, loss of glomerular function [24,25].…”
Section: Renal Lesions In Type 1 Diabetesmentioning
confidence: 99%
“…However, in advanced stages of the disease, interstitial, tubular and glomerulo-tubular junction injuries drive the progression towards ESRD [24,25].…”
Section: Renal Lesions In Type 1 Diabetesmentioning
confidence: 99%
“…may contribute to the decline in GFR [25]. There are no published data on type 2 diabetes, but it is possible that there are fewer atubular glomeruli resulting in better preservation of GFR; or conversely, that there is a higher frequency of atubular glomeruli resulting in glomerular enlargement of the remaining functional glomeruli and subsequent preservation of GFR.…”
Section: Is Glomerular Enlargement a Compensatory Mechanism?mentioning
confidence: 99%